2020
DOI: 10.3892/or.2020.7611
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of KRT17 decreases osteosarcoma cell proliferation and the Warburg effect via the AKT/mTOR/HIF1α pathway

Abstract: Keratins are fibrous structural proteins that serve essential roles in forming the stratum corneum and protect the cells in this layer of skin from damage. Keratin 17 (KRT17) is a key member of the keratins, and dysregulated expression of KRT17 has been reported in various types of cancer, such as lung and gastric cancer. The present study aimed to identify the role of KRT17 in osteosarcoma and the underlying molecular mechanism. The expression of KRT17 in osteosarcoma tissues and cell lines was detected using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…It was reported that KRT17 deficiency impairs the activation of ERK, while makes little difference on AKT activation in pancreatic cancer cells [21], which disagrees with our present results. However, a recent in vitro and in vivo study on osteosarcoma cells have shown that KRT17 participates in the regulation of the AKT/mTOR/HIFα pathway [32]. Besides, the pro-tumor effect of KRT17 was found to be AKT-dependent in gastric cancer [33], as well as in esophageal squamous cell carcinoma [34].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that KRT17 deficiency impairs the activation of ERK, while makes little difference on AKT activation in pancreatic cancer cells [21], which disagrees with our present results. However, a recent in vitro and in vivo study on osteosarcoma cells have shown that KRT17 participates in the regulation of the AKT/mTOR/HIFα pathway [32]. Besides, the pro-tumor effect of KRT17 was found to be AKT-dependent in gastric cancer [33], as well as in esophageal squamous cell carcinoma [34].…”
Section: Discussionmentioning
confidence: 99%
“… 16 A recent study reported that knockdown of KRT17 may be an effective method to treat osteosarcoma by inhibiting the proliferation of osteosarcoma cells and inhibiting the Warburg effect of Akt/mTOR/HIF1-α pathway. 17 KRT17 was initially studied in basal cell carcinoma of the skin, which belongs to type I keratin family with a molecular weight of about 48kd. 18 Existing studies have shown that KRT17 is involved in the occurrence and development of a variety of tumors or guide the different prognosis of many tumors, such as colorectal cancer, 19 gastric cancer, 20 cervical cancer, 21 renal cell carcinoma, 22 pancreatic cancer, 23 non-small cell cancer, 24 etc.…”
Section: Introductionmentioning
confidence: 99%
“…This energy metabolic reprogramming promotes energy generation and thus facilitates OS cells proliferation, invasion, and chemoresistance [19]. Several factors including glycolytic enzymes (e.g., GLUT1), oncogenes (e.g., KRT17), transcription factors (e.g., HIF1α), tumor suppressors (e.g., p53), and related signaling pathways have been reported to regulate the glycometabolism in OS cells and play pivotal roles in overall survival of patients [20][21][22]. These factors may help formulate therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%